Stellate Ganglion Block as Pain Management in Post Herpetic Neuralgia: A Case Report - Abd. Samad Amin (HM Publisher, 2022)
Introduction: Stellate ganglion block (SGB) has been used in various conditions. Medical conditions include complex regional pain syndrome and peripheral vascular disease. This study aims to describe the use of stellate ganglion block for pain management in post-herpetic neuralgia. Case presentation: A 68-year-old man came with a complaint of severe headache. Complaints of severe headache since 1 month ago, pain until tears come out. This complaint is accompanied by red blisters, pain on the left side of the face, weakness, and decreased appetite. Physical examination showed compos mentis consciousness, appeared moderately ill, blood pressure 160/90 mmHg, heart rate 112x/minute, respiratory rate 20x/minute, temperature 37.2oC, numeric rating scale 7/10. In the head region, there was cicatricial, paresis of N VII, positive hypersensibility, positive allodynia, spasm neck muscles, right joint shoulder stiffness, and stiffness in the m. right rotator cuff. The patient was given intervention in the form of a stellate ganglion block (SGB). Follow-up 1 day after the GBS procedure showed that the headache and left facial pain were greatly reduced. Conclusion: Ultrasonographic-guided stellate ganglion block can reduce post-herpetic neuralgia symptoms with minimal complications.